Label Halal dan Hukum Asal Bahan Pangan - Arif Al Wasim (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2016)
The consumption of halal is one of the important suggestions of the Sharia for Muslims. Nowadays, public awareness of the importance of halal consumption is increasing. The guarantee of foodstuffs in Indonesia is halal certificates and labels as regulated in Undang-Undang No. 33 tahun 2014 on Guarantee of Halal Products. Not all of food products circulating and distributed in Indonesia has halal certificates and labels. This study was conducted to assess the assurance of halal food that does not have halal certificates and labels, and how to consume it in dealing with the law of sharia. The study was conducted with approach of Jurisprudential Rules (Qawâ’id Fiqhiyyah), focusing the discussion of the status of